Dynamical observation of photo-Dember effect on semi-insulating GaAs using femtosecond core-level photoelectron spectroscopy. (30th January 2015) - Oguri, Katsuya; Tsunoi, Takanobu; Kato, Keiko; Nakano, Hidetoshi; Nishikawa, Tadashi; Tateno, Kouta; Sogawa, Tetsuomi; Gotoh, Hideki
Abstract: We investigated ultrafast photogenerated carrier dynamics on a semi-insulating GaAs surface using femtosecond time-resolved core-level photoelectron spectroscopy. We observed a transient change in the surface potential where the Ga-3d core-level peak instantaneously shifted by ∼350 meV toward a higher binding energy within 2 ps of a 100 fs laser irradiation. A comparison of the experimental results with numerical simulations based on a drift-diffusion model of a semi-insulating semiconductor revealed that the transient surface potential change was mainly due to the photo-Dember effect, whereby the large difference in the carrier diffusion between the electron and hole instantaneously induced a surface photovoltage.